EVALUATING GERMAN CHAMOMILE'S ACTIVITY AGAINST ENTEROCOCCUS FAECALIS ISOLATED FROM ROOT CANALS - Yaseen, A.; Mahdee , A.; Mohmmed , S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
This study was aimed to investigate German chamomile extract's active ingredients and their antibacterial activity against Enterococcus faecalis (E. faecalis) which was previously isolated from root canals. Chamomile hydroalcoholic extract was obtained by maceration process. Phytochemical tests and thin layer chromatography (TLC) used to detect active ingredients in the extract. Agar well diffusion method was used to compare antimicrobial effect of 3% sodium hypochlorite (NaOCl) and 4 extract's concentrations (100mg/mL-400mg/mL) against E. faecalis. Chamomile's anti-biofilm effect against E. faecalis biofilm was tested by microtiter plate assay with ELISA reader. Phytochemistry showed that, tannins, glycosides, alkaloids, flavonoids, and polyphenolic chemicals were abundant. TLC revealed presence of phenolic compounds including; caffeic acid, chlorogenic acid, and others, and flavonoids such as; apigenin, catechin, and others. Agar well diffusion showed higher inhibition zone diameter for 200mg/mL, 300mg/mL, and 400mg/mL chamomile in comparison to 3% NaOCl. The extract showed strong E. faecalis biofilm inhibition by all its concentrations, while moderate inhibition exerted by NaOCl. It can be concluded that German chamomile extract appears rich antimicrobial and effective inhibitor against E. faecalis biofilm.